Unpredictable Malnutrition and Short-Term Outcomes after Single Anastomosis Sleeve Ileal (SASI) Bypass in Obese Patients - Ayman Kamal; Mahmoud El Azawy; Tarik A. A. Hassan (Hindawi Limited, 2023)
Background/Introduction. The single anastomosis sleeve ileal (SASI) bypass is a novel metabolic/bariatric surgery operation based on minigastric bypass operation and Santoro's operation. Objectives. The aim of this study is to present the clinical outcomes of SASI bypass as a treatment alternative for patients with morbid obesity. Methods. This study was a prospective follow-up of morbidly obese patients who underwent SASI bypass at Helwan University Hospital between March 1, 2019, and March 2020. The surgical procedure involved sleeve gastrectomy, followed by the anastomosis of the ileum, which was brought and hand-sewn 4 cm length side to side with the antrum, at a distance of 250 cm from the ileocecal valve. The data collected for the study included the resolution of comorbidities, incidence of gallstones, and one-year morbidity. Results. The mean age of the studied patients (n = 30) was 44.13 ± 8.9 years. The mean BMI of the studied patients was 47.3 ± 7.6 kg/ht2. All patients were morbidly obese for an average of 24 years. Postoperatively, 48% of the patients (n = 13) developed gallstones (GS), and the formation of GS was significantly higher in patients with longer durations of obesity (P = 0.009) and rapid weight loss. There was a significant decrease in the incidence of GS after 12 months postoperatively (P < 0.05). 63% of the patients (n = 19) had malnutrition, and 15 cases required revision due to the fear of further weight loss. Revision and malnutrition were significantly higher among male patients than female patients and among patients with longer durations of obesity (P ≤ 0.001). Conclusion. The SASI bypass may be an effective bariatric and metabolic surgery that can achieve satisfactory weight loss and improvement in medical comorbidities. However, our study highlights the potential risks of severe malnutrition and unpredictable weight loss; patient selection and duration of obesity may play a role in mitigating these risks.